CD4+CD25highCD127low/-FoxP3+ Regulatory T-Cell Population in Acute Leukemias: A Review of the Literature. (3rd March 2019) - Niedźwiecki, M.; Budziło, O.; Adamkiewicz-Drożyńska, E.; Pawlik-Gwozdecka, D.; Zieliński, M.; Maciejka-Kembłowska, L.; Szczepański, T.; Trzonkowski, P.
Abstract : Regulatory T-cells (Tregs) are a very important subtype of lymphocytes when it comes to self-control in the human immunological system. Tregs are decisive not only in the protection against destruction of own tissues by autoimmune immunocompetent cells but also in the immunological answer to developing cancers. On the other hand, Tregs could be responsible for the progression of acute and chronic leukemias. In our study, we review publications available in the PUMED database concerning acute leukemia, with a particular emphasis on child's leukemias. The percentage of regulatory T-lymphocytes in peripheral blood and bone marrow was elevated compared to those in healthy individuals and correlated with progressive disease. Regulatory T-cells taken from children diagnosed with leukemia showed a higher suppressive capability, which was confirmed by detecting elevated levels of secreted IL-10 and TGF-beta. The possibility of pharmacological intervention in the self-control of the immunological system is now under extensive investigation in many human cancers. Presumably, Treg cells could be a vital part of targeted therapies. Routine Treg determination could be used to assess the severity of disease and prognosis in children with acute lymphoblastic leukemia. This proposition results from the fact that in some studies, higher percentage of Treg cells in peripheral blood was demonstrated. However, observations confirming these facts are scarce; thus, extrapolating them to the population of children with hematological malignancies needs to be verified in additional studies.